Ethnic variations in the childhood prevalence of Hirschsprung disease in New Zealand. Issue 10 (3rd October 2018) - Taghavi, Kiarash; Goddard, Lucy; Evans, Stephen M.; Hobson, Andrew; Beasley, Spencer W.; Sankaran, Sasikumar; Kukkady, Askar; Stevenson, Jonathan; Stringer, Mark D.
Abstract : Background: Epidemiological studies have suggested that there may be ethnic variations in the prevalence of Hirschsprung disease (HD) but no study has systematically investigated this issue or potential ethnic variations in the extent of aganglionosis in HD. This study aimed to investigate this in a childhood population in New Zealand. Methods: A multicentre national retrospective review was undertaken of all newly diagnosed cases of HD at each of the four paediatric surgical centres in New Zealand over a 16‐year period (January 2000 to December 2015). Original histological, radiological and operative reports were obtained and analysed. Self‐identified ethnicity was recorded from admission documents. Birth statistics were obtained from Statistics New Zealand. Results: A total of 246 cases of HD were identified. The prevalence of HD was 1:3790 live births for European, 1:6610 among Māori, 1:1834 among Pacific Peoples, 1:3847 among Asian and 1:5694 among Middle Eastern. The prevalence of HD was statistically significantly greater in Pacific Peoples ( P  < 0.0005). The proportion of children with long‐segment HD was also significantly greater in Pacific and Asian populations than others ( P  = 0.04). These findings were not due to differences in the proportion of familial cases of HD among the different populations. Conclusions: The prevalence and phenotype of HD varies significantly between different ethnic groups within New Zealand. This may well be related to variations in the frequencies of HD‐associated gene mutations within these populations.